2006
DOI: 10.1074/jbc.m604589200
|View full text |Cite
|
Sign up to set email alerts
|

Large Store-operated Calcium Selective Currents Due to Co-expression of Orai1 or Orai2 with the Intracellular Calcium Sensor, Stim1

Abstract: The molecular nature of store-operated Ca 2؉ -selective channels has remained an enigma, due largely to the continued inability to convincingly demonstrate Ca 2؉ -selective store-operated currents resulting from exogenous expression of known genes. Recent findings have implicated two proteins, Stim1 and Orai1, as having essential roles in store-operated Ca 2؉ entry across the plasma membrane. However, transient overexpression of these proteins on their own results in little or no increase in store-operated ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

45
519
8
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 502 publications
(580 citation statements)
references
References 36 publications
(42 reference statements)
45
519
8
8
Order By: Relevance
“…Using elegant screening approaches including positional cloning from the SCID patients, Feske and colleagues [14] have shown that a member of a new class of proteins, called ORAI (keepers of gates of heaven, from Greek mythology), is part of the CRAC channel complex. A similar conclusion was independently reached by others [15][16][17][18], who in addition showed that ORAI1 increased CRAC currents if expressed with the CRAC activator STIM1. STIM1 has been previously shown to mediate CRAC activation after Ca 2+ store depletion [19][20][21][22].…”
Section: Introductionsupporting
confidence: 81%
“…Using elegant screening approaches including positional cloning from the SCID patients, Feske and colleagues [14] have shown that a member of a new class of proteins, called ORAI (keepers of gates of heaven, from Greek mythology), is part of the CRAC channel complex. A similar conclusion was independently reached by others [15][16][17][18], who in addition showed that ORAI1 increased CRAC currents if expressed with the CRAC activator STIM1. STIM1 has been previously shown to mediate CRAC activation after Ca 2+ store depletion [19][20][21][22].…”
Section: Introductionsupporting
confidence: 81%
“…First, we compared the fluorescence recovery after photobleaching (FRAP) of STIM1-CFP in unstimulated cells resting on a polylysine surface to that of STIM1-CFP in caps. We studied cells cotransfected with STIM1-CFP and untagged Orai1, because cotransfection of these two proteins is required for increased CRAC channel function (Mercer et al, 2006;Peinelt et al, 2006;Soboloff et al, 2006;Zhang et al, 2006). There was clear recovery of fluorescence from STIM1-CFP in the ER of unstimulated cells resting on polylysine, but little recovery of STIM1-CFP fluorescence when the bleached region was part of a cap structure in stimulated cells (Figure 3, A and C).…”
Section: The Mobility Of Stim1-cfp and Orai1-yfp Decreases In The Capsmentioning
confidence: 99%
“…Initial experiments showed that depletion of Ca 2ϩ stores causes translocation of STIM1 into puncta near the PM with kinetics that precede channel opening (Liou et al, 2005;Roos et al, 2005;Mercer et al, 2006;Wu et al, 2006;Liou et al, 2007), and that these puncta appear to correspond to sites of local Ca 2ϩ entry . STIM1 and Orai1 colocalize in these puncta Xu et al, 2006;Li et al, 2007), and aggregation of STIM1 can induce clustering of Orai1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations